Joy and sorrow and the like in the poetic language of Klopstock, Schiller and Goethe - Schwarzschild, Agathe (The University of Edinburgh, 1940)
I . INTRODUCTION: 1. "Inner Form of Language" . 2. Study of synonyms. 3. Reasons for choice of words to be analysed- II. THE METHOD EMPLOYED AID ITS JUSTIFICATION: 4. Necessity of studying synonyms in definite particular contexts. 5. Connection between sound -body and meaning due to a trace. 6. Complexity of meaning. 7. Definiteness of meaning, illustrated by Goethe's "Jagers Abendlied". 8. "Intelligible" and "knowable" meaning. 9. Categories of analysis. III. TABLES OF ANALYSED WORDS AND THEIR INTERPRETATION: 10. Words of joy (in alphabetical order) . 11. Words of sorrow (do.) IV. CONCLUSION: 12. Change of meaning in general: creative act of speech, receptivity, intelligible and knowable meaning. 13. Particular changes of meaning and their causes. EDITIONS USED: Klopstock: Inselverlag. Schiller: Meyers Klassiker. (some poems: Sakularausgabe) + Goethe: Meyers Klassiker. (some poems: Jubilaumsausgabe; some poems: from West-Ust1, Divan,Ostl, Divan, only by title; Stella and Glavigo by acts).+

+ All quotations not taken from Mezers Klasiker are bracketed.